2007
DOI: 10.1097/01.tp.0000296019.85986.af
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Tube and Gel Techniques for ABO Antibody Titration, as Performed in Three European Centers

Abstract: Data from 60 consecutive ABO-incompatible kidney transplantations performed in Stockholm, Sweden; Freiburg, Germany; and Uppsala, Sweden, revealed significant variation in preoperative A/B antibody levels, with median titers of 1:32, 1:128, and 1:8, respectively. We wanted to investigate whether these differences were method-related. The same samples from 21 healthy blood donors were analyzed in the three centers using current local methods. Results confirmed method-related differences, with higher A/B titers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 7 publications
5
88
0
3
Order By: Relevance
“…In addition to this, an extensive titer validation test was performed among the centers of Stockholm, Uppsala and Freiburg using the same samples from 21 healthy volunteers. By using the gel technique, a median deviation of only one titer step was observed between these three facilities [12].…”
Section: Discussionmentioning
confidence: 98%
“…In addition to this, an extensive titer validation test was performed among the centers of Stockholm, Uppsala and Freiburg using the same samples from 21 healthy volunteers. By using the gel technique, a median deviation of only one titer step was observed between these three facilities [12].…”
Section: Discussionmentioning
confidence: 98%
“…These variations seemed to be due to different techniques between laboratories, but considerable variation was still noted after standardization of techniques. Another report also showed a large variation of isoagglutinin titers (a median three-fold difference) among three centers performing ABO-I kidney transplants in Germany and Sweden (Kumlien et al, 2007). In this report, gel hemagglutination technique significantly decreased inter-center difference (a median one titer difference) compared with tube methods.…”
Section: Conventional Tube Methodsmentioning
confidence: 51%
“…The gel or bead particles trap the RBC agglutinates as a filter during centrifugation. The agglutination is graded from 0 to 4 +, and inverted value of the highest plasma dilution that gives a 1+ agglutination reaction is interpreted as the titer (Kumlien et al, 2007).…”
Section: Gel or Bead Column Agglutinationmentioning
confidence: 99%
“…One recent study tried to minimize such method variation but was only able to reduce the variation in titer testing for the AHG phase determination with the tube technique (28). Importantly, Kumlein et al (29) found that the gel hemagglutination technique significantly decreased inter-transplant center titer variation compared with the tube method. Bentall et al (30) recommended a reference method for titration with an antibody standard as a way to improve comparability of titers between transplant programs.…”
Section: Subgrouping Of a And Ab Donorsmentioning
confidence: 99%